Medication errors in a health care facility in southern Saudi Arabia - Alshahrani, Sultan M.; Alakhali, Khaled M.; Al-Worafi, Yaser Mohammed (Tropical Journal of Pharmaceutical Research, 2019)
Purpose: To identify medication errors at Aseer Central Hospital (ACH, Abha) in the southern province of Saudi Arabia. Methods: A cross-sectional retrospective study was conducted by reviewing adult patients records (> 15 years old) at ACHs inpatient and outpatients settings over an 8-week period in October and November 2015. Results: We identified 113 medication errors, including 112 prescribing errors and 1 dispensing error. Most medication errors (91.2 %) in this study were for inpatient prescriptions. The most common prescribing error was medication duplication (31.2 %) followed by missing patient identifying information (25 %). Conclusion: Medication errors, mainly in inpatient prescriptions, have been fully identified at ACH. Educational interventions such as workshops could help minimize and prevent medication errors.